Usefulness of an in vitro-transcribed RNA control for the detection and quantification of Yellow fever virus through real-time reverse transcription-polymerase chain reaction (2024)
ABSTRACT: Introduction: Unvaccinated individuals in endemic areas with proven enzootic transmission of Yellow fever virus are at risk of infection due to a dramatic shift in the epidemiology of the disease over recent years. For this reason, epidemiological surveillance and laboratory confirmation of cases have become mandatory. Objective: To develop and test a control RNA for YFV detection through real-time RT-PCR. Methods: A 437-bp insert containing the T7 promoter and the target sequences for two different in-house protocols was designed in the context of the pUC57 vector and obtained through gene synthesis. After T7-driven in vitro transcription, standard curves were developed for Log10 serial dilutions of the YFV control RNA with 8 replicates. Results: A dynamic range of quantification of 10 orders of magnitude was observed with a limit of detection of 6.3 GCE/µL (95% CI, 2.6 to 139.4 GCE/µL). Conclusion: The plasmid construct is available for YFV molecular test validation on clinical, entomological, and epizootic samples. Keywords: In vitro transcription; Molecular detection; Plasmid DNA; RT-qPCR; Yellow fever virus.